Role of Digital Marketing and Digital Transformation in the SME’s Financial Performance - Toni, Nagian; Goh, Thomas Sumarsan; Nyoto, Nyoto; Hong, Rita (Politeknik APP Jakarta, 2024)
The aim of this research is to analyze the relationship between digital marketing and financial performance, analyze the relationship between digital transformation and financial performance and analyze the relationship between digital transformation and digital marketing. This research method is quantitative through surveys, the research population is SMEs owners in Indonesia. The results of data analysis show that digital marketing has a positive and significant relationship to financial performance, digital transformation has a positive and significant relationship to financial performance, digital transformation has a positive and significant relationship to digital marketing. The results of the mediation effect test on the influence of digital marketing on financial performance through digital transformation mediation can be concluded that digital transformation is full mediation on the influence of digital marketing on financial performance.